Relationship between Goal-Orientation Culture and Job Commitment among Lecturers in Public Universities in Kenya (International Journal of Scientific Research and Management (IJSRM), 2023)
One of the management strategies which guides people and organizations to focus their efforts towards achievement of individual and organizational objectives is goal orientation. While it has been documented by previous researchers that learning goal as well as performance goal orientations are significant in influencing employee behaviour, how the same influence job commitment among university lecturers is still a matter of conjecture. This knowledge would be significant especially in the context of public universities in Kenya where missing lecture sessions are rampant on one hand, while more employers prefer graduates from Technical, Industrial and Vocational Enterprise Training (TIVET) institutions than university graduates, on the other hand. This study explored the influence of goal orientation culture on job commitment among lecturers at the University of Nairobi and South Eastern University. The hypothesis that: Organizational goal orientation culture does not have significant relationship with job commitment among lecturers at the Nairobi University and South Eastern Kenya University was tested. Self-determination theory (SDT) of motivation originated by Ryan and Deci was used to guide the study. Descriptive survey design was used on a target population of 56191 lecturers, Deans and students from which 377 was derived as a sample size via Krejcie and Morgan’s (1970) Table. Closed and open-ended questionnaire was used for data collection, and regressions (at 0.05 level of significance) as well as thematic analyses used respectively to analyse quantitative and qualitative data. Findings revealed that 86.1% of changes in job commitment among the lecturers is attributed to goal-oriented culture (R2 =0.861), with goals related to timelines for examination result submission and number of units taught strictly adhered to. It is concluded that matching of the university and lecturers’ goals related to teaching timelines among others significantly enhance lecturers’ job commitment. Professional development opportunities for lecturers should be enhanced to improve their capacities, while challenges facing lecturers in enhancing their job commitment need further exploration.